Upaya Meningkatkan Motivasi Belajar Siswa Melalui Layanan Bimbingan Kelompok pada Siswa MTS Negeri 2 Deli Serdang - Khairunnisa Sulistiyaningrum; Ahmad Syarqawi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to explore how team leadership is implemented. works in increasing student motivation, considering the number of participants in this study reached 8 students in class VII MTs Negeri 2 Deli Serdang, North Sumatra. This type of research uses a quasi-experimental design and a non-parametric research design. The experimental model is used for the experiment technique. The results of the study proved that the experimental group based on the results of the Wilcoxon, M. (2-sided) test for the control group was found to be 0.000 <0.05 and there was a difference in the values before and after in the control group. From the results of the Wilcoxon test it is known that the M (2-sided) of the experimental group is 0.000 <0.05 which indicates a difference in the values before and after in the experimental group.